Reference values for handgrip strength and their association with intrinsic capacity domains among older adults. Issue 2 (6th March 2019) - Ramírez‐Vélez, Robinson; Correa‐Bautista, Jorge Enrique; García‐Hermoso, Antonio; Cano, Carlos Alberto; Izquierdo, Mikel
Abstract: Objective: The purposes of this study were three‐fold: (i) to describe handgrip strength in older individuals aged ≥60 years in Colombia; (ii) to identify sex‐specific and age‐specific muscle weakness cut‐off points in older adults; and (iii) to determine the odds of adverse events for each of the intrinsic capacity domains for individuals with handgrip strength greater than the muscle weakness cut‐off points, as compared with their weaker counterparts. Methods: A cross‐sectional study was conducted in Colombia, among 5237 older adults aged ≥60 years old (58.5% women, 70.5 ± 7.8 years), according to 'SABE Survey 2015'. Handgrip strength data were obtained with a Takei dynamometer. Sociodemographic variables, five domains of intrinsic capacity (i.e. locomotion, vitality, cognition, psychological, and sensory), and medical conditions were assessed and analyzed. Adjustments variables were age, ethnicity, socio‐economic status, urbanicity, body mass index, smoking status, alcohol intake, drug use, physical activity, and co‐morbid chronic diseases. Sex‐stratified analyses were conducted with logistic regression models. Results: Handgrip strength was greater among men than among women (26.7 ± 8.5 vs. 16.7 ± 5.7 kg, respectively, P < 0.001) at all ages. Weak handgrip strength cut‐off points ranged from 17.4 to 8.6 and from 10.1 to 4.9 in men and women, respectively. Overall, participants with optimal handgrip strength had better intrinsic capacity [in men, odds ratio (OR) = 0.62, 95% confidence interval (CI) 0.53 to 0.71; P < 0.001; and in women, OR = 0.79, 95% CI 0.68 to 0.92; P = 0.002] than their weaker counterparts. Also, men with optimal handgrip strength had a lower risk of hospitalization (OR = 0.47, 95% CI 0.29 to 0.78; P = 0.004) than their weaker counterparts. Conclusions: This study is the first to describe handgrip strength values and cut‐off points for muscle weakness among a nationally representative sample of Colombian older adults by age and sex. After categorizing older adults as weak or not weak based on the handgrip cut‐off points, non‐weakness was associated with a decreased odds of intrinsic capacity impairments. These cut‐off points may be good candidates for clinical assessment of risks to physical and mental health in older Colombian adults.